Pteropodids associated with Durian inflorescence in selected areas of Tagum City and Davao City - Delima, Aileen Grace D. (2008)
Pteropodids visiting durian inflorescence were sampled to determine the species composition of bats suspected to be pollinators of durian. Mist netting was conducted between the months of April and June in five farms located in Tagum City (2 farms) and Davao city (3 farms). A total of six species were captured, three of which are Philippine endemics (E), including the following: Macroglossus minimus, Eonycteris spelaea, Rousettus amplexicaudtus, cynopterus brachyotis (E) Haplonycteris fischeri (E), and Ptenochirus jagori (E). out of the six species, P. jagori (28%) appears to be the most abundant followed by M. minimus (24%), C. brachyotis (19%), E. spelaea (12%), H. fischeri (9%), and the least was R. amplexicaudatus (8%). In comparing the two agricultural sites, 66.69% similarity was recorded since R. amplexicaudatus was not captured in Tagum City. Population size was estimated only in three sites.: San Miguel (N=257.3), Wangan (N=215) and Los Amigos (N=156.5). the sex ratio of the captured fruit bats favored for C. brachyotis. Adult bats were also frequently captured than juveniles. The presence of these species strongly indicates that they play an important role in durian flower pollination
Thesis (BS Biology) -- University of the Philippines Mindanao, 2008
Keywords: Durian; Mist netting; Pteropodids; Pollination